1990
DOI: 10.1111/j.1476-5381.1990.tb14138.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural evidence for functional interactions between 5‐HT‐receptor subtypes in rats and mice

Abstract: 1 Different 5-hydroxytryptamine (5-HT) receptor subtypes mediate different behavioural responses. Compounds acting at more than one 5-HT receptor exert behavioural effects which may be the result of response competition or a specific interaction between pathways within the CNS. Therefore the mutual interaction between different 5-HT receptor subtypes was studied.2 Hypothermia and hypoactivity in mice induced by the 5-HTlA-agonist 8-hydroxy-dipropylaminotetralin (8-OH-DPAT) could be attenuated by the preferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(57 citation statements)
references
References 25 publications
(38 reference statements)
2
55
0
Order By: Relevance
“…They are highly colocalized (80%) in pyramidal neurons of the PFC (Santana et al, 2004) and electrophysiological studies have shown that M100907 potentiate 8-OH-DPAT suppression on firing rate (Ashby et al, 1994). In addition, 5-HT 2A receptor antagonists ICI 180,809 and ritanserin potentiate the 5-HT syndrome produced by 8-OH-DPAT Sharp et al, 1990) whereas 8-OH-DPAT inhibits head twitching behavior induced by systemic DOI (Berendsen and Broekkamp, 1990;Darmani et al, 1990;Dursun and Handley, 1993) or microinjection into the mPFC of (À) DOB, a congener of DOI and a 5-HT 2A/2C receptors agonist (Granhoff et al, 1992). Clearly, the opposition between the two 5-HT receptor subtypes suggests that the improvement produced by M100907 and 8-OH-DPAT on CPP-induced accuracy deficit may result from a functionally antagonistic activity of these receptors on a common intracellular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…They are highly colocalized (80%) in pyramidal neurons of the PFC (Santana et al, 2004) and electrophysiological studies have shown that M100907 potentiate 8-OH-DPAT suppression on firing rate (Ashby et al, 1994). In addition, 5-HT 2A receptor antagonists ICI 180,809 and ritanserin potentiate the 5-HT syndrome produced by 8-OH-DPAT Sharp et al, 1990) whereas 8-OH-DPAT inhibits head twitching behavior induced by systemic DOI (Berendsen and Broekkamp, 1990;Darmani et al, 1990;Dursun and Handley, 1993) or microinjection into the mPFC of (À) DOB, a congener of DOI and a 5-HT 2A/2C receptors agonist (Granhoff et al, 1992). Clearly, the opposition between the two 5-HT receptor subtypes suggests that the improvement produced by M100907 and 8-OH-DPAT on CPP-induced accuracy deficit may result from a functionally antagonistic activity of these receptors on a common intracellular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…19, NO. 5 ( Arnt and Hyttel 1989;Berendsen and Broekkamp 1990) and attenuated by co-administration of the 5-HT 2C receptor agonists MK 212 and mCPP (Berendsen and Broekkamp). An alternative explanation for the modest effect of chronic DOI treatment on 8-OH-DPAT-induced hypothermia and forepaw treading may be the partial agonist activity of DOI.…”
Section: Discussionmentioning
confidence: 99%
“…DOI, with equal affinity for members of the 5-HT 2 receptor family, may activate 5-HT 2 receptors that have opposing effects on these 5-HT 1A receptor-mediated behaviors. For example, forepaw treading in rats induced by 8-OH-DPAT is potentiated by co-administration of DOI (Arnt and Hyttel 1989;Berendsen and Broekkamp 1990) and attenuated by co-administration of the 5-HT 2C receptor agonists MK 212 and mCPP (Berendsen and Broekkamp). An alternative explanation for the modest effect of chronic DOI treatment on 8-OH-DPAT-induced hypothermia and forepaw treading may be the partial agonist activity of DOI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, both flattened body posture and hypothermia, two behaviors elicited by 5-HT 1A receptor agonists, are reduced when 5-HT 2 receptor agonists are administered together with 5-HT 2 receptor agonists [2,5]. Consistent with our findings that VMN infusion with DOI prevented the lordosis-inhibiting effect of 8-OH-DPAT [40], addition of the 5-HT 2 receptor agonist, DOI, to tissue slices of the VMN attenuated the inhibitory effects of 5-HT 1A receptor agonists on neuronal firing [19].…”
Section: Introductionmentioning
confidence: 99%